EFFECTIVENESS OF COMPETENCY TRAINING IN IMPROVING EMPLOYEE PERFORMANCE OF PT KARYA ENERGI INDONESIA (CASE STUDY ON MAINTENANCE TEAM) - Munawir Maulana, Muchamad; Kurnia M, Fakhruddin (Jurnal Manajemen Dan Bisnis, 2025)
This study aims to examine the effectiveness of competency training in improving employee performance, specifically within the maintenance team at PT Karya Energi Indonesia. The research employs a descriptive qualitative method, which seeks to provide an in-depth understanding of the impact of training on employee performance based on field data. Data collection techniques include observation and in-depth interviews with employees and maintenance team supervisors. The results show that competency training has a significant impact on two main aspects: the improvement of technical skills and the enhancement of safety awareness. The improvement in technical skills is reflected in an 80% achievement rate within the scope of work, indicating enhanced employee capabilities in maintenance activities. Meanwhile, safety awareness increased by 85%, indicating the success of the training in fostering a culture of safe working practices. Based on these findings, continuous and relevant training is essential to maintain and improve the quality of employee performance in the future.